Welcome to a new journal! - Bajracharya, Dayananda (Himalayan Journal of Sciences, 2006)
The good news is that despite many limitations from national to individual level, there is a rise in research activities in Nepal. But the bad news is that the lack of standard and regular scientific journals within the country always discourages researchers when they prepare to publish their findings. This journal should be effective towards meeting the dire need of the researchers.Himalayan Journal of Sciences 1(1): 1, 2003The full text is of this article is available at the Himalayan Journal of Sciences website